Configurações subjetivas dos servidores da Receita Federal diante da ideologia gerencialista - Juliana de Fátima Pinto (2018)
Managerialism has been present in the Brazilian Public Administration for more than twenty years. Despite the changes of the Political Parties, there has never been a break with this orientation, especially for the Typical Careers of State. From this viewpoint, this study aimed to understand the shared subjective configurations of the Federal Revenue Service's server in a work space marked by the hegemony of managerialist ideology. The problem raised during the research was established in the following question: How are the subjective senses of the Brazilian Federal Revenue servants organized in an institution that has been investing in the improvement of the managerial model? The epistemology used for the construction of this work was the Theory of Subjectivity of Fernando Luís González Rey (2003; 2005a). The reference that served as orientation for the accomplishment of the research is articulated by three perspectives: the managerialist ideology, the suffering in the work and the theory of the subjectivity. All of them are focusing on the social space of work. The method chosen was the case study. The research was done in the 6th Tax Region of the Brazilian Federal Revenue Service, at Belo Horizonte, from 2016 to 2017. Empirical data were produced through conversations with six Federal Revenue Service, three tax analysts and three tax auditors, observing the qualitative methodology of González Rey. Informal moments with other servers were also used to collect hypotheses, as well as the academic production, legislations and reports that had relation with the institution searched. During the research, five main subjective configurations were defined: "competitiveness by attributions", "productivity bonus", "union membership", "technological changes", "dissatisfaction in the RFB", forming a tangle of senses that permeate through isolation, insecurity , inequalities, etc. It was concluded that managerialism permeates the subjective configurations of the servers. In this way, it is necessary to give voice to the singularities to construct alternatives that break with the conflicts, rivalries and sufferings present in the social subjectivity of the RFB